Analyzing the roles of human U1 snRNA variants in pre-mRNA processing. - Goh, Eling. (2013)
Splicing and polyadenylation are two essential steps in pre-mRNA processing. During splicing, U1 snRNP binds to a diversity of 5’ splice sites (5’ss) with its 5’ end. However, there remains a number of 5’ss that could not be bound optimally by the U1 snRNP. Very recently, U1 snRNA class I pseudogenes have been re-classified as human U1 snRNA variants due to several reasons: (i) actively transcribed U1-like snRNA genes were discovered; (ii) one of the U1 variants was shown to suppress intronic polyadenylation (IPA); and (iii) these U1 variants are packaged into snRNPs. Interestingly, nine of these U1 variants have different 5’ends as compared to the major U1. Hence, we hypothesized that a subset of 5’ss in the human genome could be recognized by these U1 variants. Chimeric U1 suppressors were generated to analyze the role of human U1 variants in splicing and they failed to rescue splicing of CD46 exon 8 efficiently. However, consistent with previous findings, knocking down of endogenous U1 variants had resulted in a surge of intron-retained products indicative of IPA. Therefore, U1 variants are most likely not involved in 5’ss recognition but could have significant roles in IPA.